Effectiveness of Guided Discovery Model Based on Blended Learning to Improve Learning Outcomes in Ecosystem Materials. - Cendikia Hesti Ariyani; Yustinus Ulung Anggraito (Journal of Biology Education, 2024)
The blended learning strategy in biology education at SMA Negeri 11 Semarang faces challenges such as limited face-to-face time, teacher-centered methods, and limited student interaction, resulting in an uninteresting experience and low learning outcomes in Class X 2020 Final Semester Assessment (PAS) /2021 Ecosystem Topic. This study aims to analyze the effectiveness of the guided discovery model based on blended learning on students' learning interest and cognitive learning outcomes in the ecosystem topic at SMA N 11 Semarang. Using a quasi-experimental design with a non-equivalent control class, Class X MIPA 5 was the experimental class, and Class XI MIPA 6 served as the control class. The research instruments included pre-tests, post-tests, a learning interest questionnaire, and an observation sheet. The results that the experimental class showed high interest and had significant differences in cognitive learning outcomes compared to the control class. There is a positive correlation between interest and learning outcomes. The implementation of guided discovery based on blended learning on the topic of ecosystems is categorized as very high. It is concluded that the guided discovery model based on blended learning proved effective in developing students' interest and enhancing their cognitive learning outcomes in the ecosystem subject.